2014
DOI: 10.1159/000362270
|View full text |Cite
|
Sign up to set email alerts
|

Demographics and Clinical Characteristics of Multiple Sclerosis in Kuwait

Abstract: Using the MS registries in two MS clinics in Kuwait, we studied the demographics and clinical characteristics of multiple sclerosis (MS). Data of 736 patients (77.7% with relapsing remitting course) were analyzed. The mean age at onset and mean duration were 26.87 and 7.71 years, respectively. About 47.9% of patients had a disease duration ≤5 years. Cerebellar/brainstem and spinal manifestations were the presenting symptoms in 29.5 and 27.4%, of patients, respectively. The EDSS score was ≤3 in 72.8% of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
1
12
1
Order By: Relevance
“…The percentage of MS patients with family history is comparable to figures in the region as well as figures in the west (13.32% in Kuwait, 15-20% in regions such as Europe, Canada, and North America). 19,21 Compared to a previous study conducted in Saudi Arabia in 2010, where 21% of the MS patients reported familial history, 6 our data showed only 12.8% of patients reported any familial history. This suggests that the increasing prevalence of MS in Saudi Arabia is not related to the familial history.…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…The percentage of MS patients with family history is comparable to figures in the region as well as figures in the west (13.32% in Kuwait, 15-20% in regions such as Europe, Canada, and North America). 19,21 Compared to a previous study conducted in Saudi Arabia in 2010, where 21% of the MS patients reported familial history, 6 our data showed only 12.8% of patients reported any familial history. This suggests that the increasing prevalence of MS in Saudi Arabia is not related to the familial history.…”
Section: Resultscontrasting
confidence: 79%
“…Looking at the demographic findings, we observed that the female to male ratio was about 2:1.This female predominance is consistent with other universal well-established registries. 18 20 The overall percentage of MS patients with family history was 12.8% of which 6.3% had at least one sibling affected. The percentage of MS patients with family history is comparable to figures in the region as well as figures in the west (13.32% in Kuwait, 15–20% in regions such as Europe, Canada, and North America).…”
Section: Discussionmentioning
confidence: 99%
“…These findings need to be reconsidered since PRMS has been eliminated and categorized as PPMS with activity and CIS is now considered part of the spectrum of MS after the 2013 revisions by the international advisory committee on clinical trials of MS. 8 The clinical phenotype findings in our study were very similar to those found in recent studies from the United Arab Emirates and Kuwait. 31 32 …”
Section: Discussionmentioning
confidence: 99%
“…3,4 The registry was established in 2010 after combining the databases of all major hospitals including MS clinics, which together accounted for nearly 98% of the MS patients diagnosed in the country. MS patients' data were retrieved from patient records and were screened for accuracy before entering them in the registry.…”
Section: Methodsmentioning
confidence: 99%